2016
DOI: 10.1016/j.jspr.2016.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Impact of opening hermetic storage bags on grain quality, fungal growth and aflatoxin accumulation

Abstract: Purdue Improved Crop Storage (PICS) bags are used by farmers in Sub-Saharan Africa for pest management of stored grains and products, including maize. These bags hermetically seal the products, preventing exchange with external moisture and gases. Biological respiration within the bags create an environment that is unsuitable for insect development and fungal growth. This study was conducted to determine the impact of routine opening of the storage bags for maize consumption on fungal growth and aflatoxin cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(30 citation statements)
references
References 17 publications
(21 reference statements)
0
29
0
1
Order By: Relevance
“…Multiple studies have demonstrated that when grain moisture is high, yeast-like fungi proliferate on the grain surface under hermetic conditions ( Weinberg et al, 2008 ; Williams et al, 2014 ; Tubbs et al, 2016 ). In this study, the initial grain moisture was 14.0% ( Lane and Woloshuk, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have demonstrated that when grain moisture is high, yeast-like fungi proliferate on the grain surface under hermetic conditions ( Weinberg et al, 2008 ; Williams et al, 2014 ; Tubbs et al, 2016 ). In this study, the initial grain moisture was 14.0% ( Lane and Woloshuk, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that O 2 levels below 3% are most effective in controlling infestations (Navarro 1978, 2012; Moreno-Martinez et al 2000). At farm level with hermetic bags like Purdue Improved Crop Storage (PICS) bags, O 2 levels below 5% are achievable ((Baoua et al 2014; Tubbs et al 2016) and according to literature 5% also causes mortality but requires longer exposure time (Bailey 1955). …”
Section: Discussionmentioning
confidence: 99%
“…The present study is the first to measure cumulative oxygen consumption by individual insects using the OxySense 5250i. Several other studies have used the OxySense to measure oxygen levels related to reproductive behavior of female C. maculatus and maize grain quality and aflatoxin accumulation under hermetic conditions ( Tubbs et al., 2016 ; Yan et al., 2016 ). The OxySense has also been used in conjunction with acoustic studies of feeding behavior of Sitophilus oryzae (L.) ( Njoroge et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%